Combinatorial ECM Arrays Identify Cooperative Roles for Matricellular Proteins in Enhancing the Generation of TH+ Neurons From Human Pluripotent Cells - Ahmed, Maqsood; Owens, Matthew J. S.; Toledo, Enrique M.; Arenas, Ernest; Bradley, Mark; ffrench-Constant, Charles (Frontiers in Cell and Developmental Biology, 2021)
The development of efficient cell culture strategies for the generation of dopaminergic neurons is an important goal for transplantation-based approaches to treat Parkinson's disease. To identify extracellular matrix molecules that enhance differentiation and might be used in these cell cultures we have used micro-contact printed arrays on glass slides presenting 190 combinations of 19 extracellular matrix molecules selected on the basis of their expression during embryonic development of the ventral midbrain. Using long-term neuroepithelial stem cells (Lt-NES), this approach identified a number of matricellular proteins that enhanced differentiation, with the combination of Sparc, Sparc-like (Sparc-l1) and Nell2 increasing the number of TH+ neurons derived from Lt-NES cells and, critically for further translation, human pluripotent stem cells.